Task-evoked pupil responses during free-viewing of hierarchical figures in relation to autistic traits in adults - Chloe Brittenham; Antoinette Sabatino DiCriscio; Vanessa Troiani; Yirui Hu; Jennifer B. Wagner (Scientific Reports)
Abstract Sensory processing differences, particularly within the visual domain, are common in neurodevelopmental conditions, including autism. Studies examining hierarchical processing of figures containing global (i.e., gist) and local (i.e., detail) elements are inconsistent but converge on a common theme in relation to autism: slowed global processing and a locally-oriented default. We examined behavioral and pupillary responses in adults with varying levels of autistic traits during a free-viewing hierarchical processing task. Results showed that participants were both more likely and faster to report global elements, but contrary to our hypothesis, differences in level of autistic traits were unrelated to spontaneous reporting of global vs. local elements. When examining phase-based analysis of pupillary responses, participants high on autistic traits showed more early and less later constriction within trials. Further, trajectory-based pupillary analysis revealed two trajectories, one characterized by constriction and the other dilation, and results showed that the dilation group disproportionately included low traits individuals. Findings suggest that although high and low traits groups showed similar behavioral responses, visual strategies used may differ, as indicated by pupillometry. This study advances our understanding of the relationship between autistic traits and visual processing, laying groundwork for further investigations into neurodivergent visual processing mechanisms.